Postpartum Midwifery Care Management of Mrs. ‘N’ with Moderate Anaemia at Sitti Khadijah I Women and Children’s Hospital of Makassar, 2023: Manajemen Asuhan Kebidanan Post Partum Pada Ny “N” Dengan Anemia Sedang DI RSIA Sitti Khadijah I Makassar Tanggal 08 Januari S/D Maret Tahun 2023 - Zalsa, Andi Zafani; Firdayanti; Zelna Yuni Andryani (Jurnal Midwifery, 2024)
Anaemia is a deficiency in red blood cells due to low haemoglobin levels. Red blood cells serve as a means of transporting nutrients and oxygen needed for physiological and biochemical processes in every tissue of the body. The normal haemoglobin level for a pregnant woman is 11 gr%. This scientific paper aims to carry out postpartum maternal care for Mrs. ’N’ with moderate anaemia at Sitti Khadijah I Women and Children’s Hospital of Makassar in 2023 using a midwifery management approach within the midwife’s scope of practice. Based on the research results, the diagnosis of the patient moderate anaemia was conducted by assessing the patient’s history and carrying out the physical examinations and supporting tests (Hb ≤7 gr/dL). The management of moderate anaemia can be done through the administration of additional blood supplements (Iron Tablets), Vitamin C, and educating the patient about iron-rich foods. In conclusion, the appropriate and effective management of moderate anaemia, based on the evidence-based practices, involves the importance of nutritional education for pregnant woman, and the active management implementation of stage III should be conducted properly and correctly.